Palmoplantar Psoriasis- Ahead in the Race-A Prospective Study from a Tertiary Health Care Centre in South India - Venkatesan, Anandan (J Clin Diagn Res, 2015)
BACKGROUND: Psoriasis is a common and chronic T cell mediated skin disorder with varied clinico-morphological types. Most of the published studies have reported chronic plaque type psoriasis to be the commonest type. AIM: To find the incidence of palmoplantar psoriasis in a tertiary health care centre in South India. MATERIALS AND METHODS: A prospective study done over a period of six months recruiting the patients attending the Dermatology out-patient department in a tertiary health care centre. RESULTS: Incidence of palmoplantar psoriasis was found to be highest among all morphological forms of psoriasis. CONCLUSION: Incidence of palmoplantar psoriasis is under-expressed. It is actually ahead in the race.